Influence of dehydration on intermittent sprint performance - Davis, J. -K.; Laurent, C. M.; Allen, K. E.; Green, J. M.; Stolworthy, N. I.; Welch, T. R.; Nevett, M. E. (The Journal of Strength and Conditioning Research, 2015)
This study examined the effects of dehydration on intermittent sprint performance and perceptual responses. Eight male collegiate baseball players completed intermittent sprints either dehydrated (DEHY) by 3% body mass or euhydrated (EU). Body mass was reduced through exercise in the heat with controlled fluid restriction occurring 1 day before the trial. Participants completed twenty-four 30-m sprints divided into 3 bouts of 8 sprints with 45 seconds of rest between each sprint and 3 minutes between each bout. Perceived recovery status (PRS) scale was recorded before the start of each trial. Heart rate (HR), ratings of perceived exertion (RPE) (0-10 OMNI scale), and perceived readiness (PR) scale were recorded after every sprint, and session RPE (SRPE) was recorded 20 minutes after completing the entire session. A 2 (condition) × 3 (bout of sprints) repeated-measures ANOVA revealed a significant main effect of condition on mean sprint time (p = 0.03), HR (p < 0.01), RPE (p = 0.01), and PR (p = 0.02). Post hoc tests showed significantly faster mean sprint times for EU vs. DEHY during the second (4.87 ± 0.29 vs. 5.03 ± 0.33 seconds; p = 0.01) and third bouts of sprints (4.91 ± 0.29 vs. 5.12 ± 0.44 seconds; p = 0.02). Heart rate was also significantly lower (p = 0.05) for EU during the second and third bouts. Post hoc measures also showed significantly impaired (p = 0.05) feelings of recovery (PRS) before exercise and increased (p = 0.05) perceptual strain before each bout (PR) during the second and third bouts of repeated sprint work (i.e., RPE and PR) and after the total session (SRPE) in the DEHY condition. Dehydration impaired sprint performance, negatively altered perception of recovery status before exercise, and increased RPE and HR response.